The Effects Of Digital Leadership, Digital Literacy, And Digital Competency On Innovative Work Behavior Among Web3 Remote Workers In Surabaya City - Pradipta Agung Wahyu Pratama; Hujjatullah Fazlurrahman; Fresha Kharisma; Muhammad Fajar Wahyudi Rahman (CV. AFDIFAL MAJU BERKAH, 2026)
This study analyzes the influence of Digital Leadership, Digital Literacy, and Digital Competency on Innovative W This study examines the influence of Digital Leadership, Digital Literacy, and Digital Competency on Innovative Work Behavior (IWB) among Web3 remote workers in Surabaya City. The research is grounded in the transformation of remote work within the Web3 ecosystem, which presents innovation challenges due to limited spontaneous social interaction. This study addresses both a contextual gap, focusing on the underexplored population of Web3 workers, and a methodological gap by integrating three key digital factors into a single analytical framework. A quantitative approach was employed using purposive sampling, involving 70 Web3 remote workers in Surabaya. Data were analyzed using multiple linear regression with SPSS software. The results show that Digital Leadership (β = 0.330), Digital Literacy (β = 0.322), and Digital Competency (β = 0.301) have a positive and significant effect on Innovative Work Behavior (p < 0.05). Simultaneously, the variables significantly influence IWB (F = 45.646), with a coefficient of determination (R²) of 0.675, indicating that 67.5% of the variation in IWB is explained by the model. These findings confirm that the integration of digital leadership, strong digital literacy, and well-developed digital competency plays a critical role in enhancing innovative work behavior in Web3 remote work environments. The study contributes to the development of Upper Echelons Theory in the context of decentralized digital work and provides practical insights for organizations in designing effective digital talent strategies.